Dynamic Properties of a Forest Fire Model - Na Min; Hongyang Zhang; Zhilin Qu (Abstract and Applied Analysis)
The reaction-diffusion equations have been widely used in physics, chemistry, and other areas. Forest fire can also be described by such equations. We here propose a fighting forest fire model. By using the normal form approach theory and center manifold theory, we analyze the stability of the trivial solution and Hopf bifurcation of this model. Finally, we give the numerical simulations to illustrate the effectiveness of our results.